Requiring competencies of basketball coaches in Greece - Kostopoulos, N. (Biology of Exercise, 2011)
The purpose of this investigation was to identify the competencies of Basketball coaches in Greece. The current study is based on previous work done by Rodrigues et al, (11), and Tripolitsioti et al, (14,17), who measured competencies both in Portuguese basketball coaches and directors of indoor sport facilities in Greece. Two hundred and forty five basketball coaches of three Greek Divisions (first, second and third) participated in the study and completed the scale. Exploratory factor analysis revealed 5 factors consisting of 21 competency statements: Sport science/practice (6 items), communication/leadership (5 items), first aid/risk management (2 items), computer skills (4 items), and programming 4 items). Moreover, the results demonstrated that first aid and training skills were the top rated competencies, following by management and computer skills, while facility & event management were the low rated competencies. These results validate that the successful basketball coaches didn`t only have training competencies, but management, computer skills, first aid, communication, facility management and event management.